2012
DOI: 10.1177/070674371205701105
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Substance Use Disorders among Men and Women in a Nationally Representative Sample

Abstract: Objective: To examine the association between a history of 5 types of childhood maltreatment (that is, physical abuse, sexual abuse, emotional abuse, physical neglect, and emotional neglect) and several substance use disorders (SUDs), including alcohol, sedatives, tranquilizers, opioids, amphetamines, cannabis, cocaine, hallucinogens, heroin, and nicotine, in a nationally representative US adult sex-stratified sample.Method: Data were drawn from the National Epidemiologic Survey of Alcohol and Related Conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
173
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(195 citation statements)
references
References 62 publications
(77 reference statements)
17
173
0
5
Order By: Relevance
“…Potential explanations for these gender differences have include that women who use substances have often (Afifi et al, 2012;Choo et al, 2014;Verona et al, 2015;Gilchrist et al, 2015) which may contribute to the higher prevalence of mood and anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Potential explanations for these gender differences have include that women who use substances have often (Afifi et al, 2012;Choo et al, 2014;Verona et al, 2015;Gilchrist et al, 2015) which may contribute to the higher prevalence of mood and anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that being exposed to several adversities during childhood, particularly different types of violence, abuse and conflict with the parents, increases the risk of substance use in adolescence and/or adulthood 11,12,14,17,18 . The dose-response effect found in this and other studies can be linked to a number of factors that may explain the substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Although life experiences during childhood are not the only factors responsible for the greater risk for substance use, they can play a key role that deserves to be studied 11,12,13,14,15 . The occurrence of adverse childhood experiences (ACEs) has been related to a higher risk of substance use among adolescents and adults 11,12,13,14,15,16,17 . The ACEs are sources of stress that people may experience early in life, usually before the age of 18, which include multiple types of abuse (physical, sexual, and psychological), neglect, and several sorts of family dysfunction 18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В целом ряде других исследований [21][22][23][24] была уста-новлена связь между травмами детского возраста и упо-треблением наркотиков.…”
Section: злоупотребление психоактивными веществамиunclassified